2012
DOI: 10.1074/mcp.m111.011544
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Highly Conserved Histone Related Protein, Ydl156w, and Its Functional Associations Using Quantitative Proteomic Analyses

Abstract: A significant challenge in biology is to functionally annotate novel and uncharacterized proteins. Several approaches are available for deducing the function of proteins in silico based upon sequence homology and physical or genetic interaction, yet this approach is limited to proteins with well-characterized domains, paralogs and/or orthologs in other species, as well as on the availability of suitable large-scale data sets. Here, we present a quantitative proteomics approach extending the protein network of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 57 publications
13
60
0
Order By: Relevance
“…If such were the case, in the absence of PKA Rgt1 would not be able to repress SUC2 transcription and invertase levels would be high. A candidate for a cooperating protein could be histone 3, as it has been reported to interact with Rgt1 [47] and could be a substrate for PKA. However the evidence is still weak, as the interaction was identified in a high throughput experiment and phosphorylation by PKA has not been demonstrated.…”
Section: Discussionmentioning
confidence: 98%
“…If such were the case, in the absence of PKA Rgt1 would not be able to repress SUC2 transcription and invertase levels would be high. A candidate for a cooperating protein could be histone 3, as it has been reported to interact with Rgt1 [47] and could be a substrate for PKA. However the evidence is still weak, as the interaction was identified in a high throughput experiment and phosphorylation by PKA has not been demonstrated.…”
Section: Discussionmentioning
confidence: 98%
“…The Mte1-GFP fusion protein has been shown to form nuclear foci in response to replication stress Tkach et al 2012;Yimit et al 2015). Moreover, high-throughput screens have implicated Mte1 in telomere length maintenance (Askree et al 2004) and indicated that it can interact with Cmr1 (Gilmore et al 2012), a chromatin-binding protein associated with replication stress response (Choi et al 2012;Tkach et al 2012;Gallina et al 2015). In this report, we show that Mte1 is a D-loop-binding protein that interacts with the Mph1 helicase and has an antagonizing role to Mph1 in recombination outcomes by enhancing CO formation.…”
mentioning
confidence: 99%
“…In reference [12], a quantitative proteomics approach was adopted to extend the protein network of core histones (H2A, H2B, H3 and H4) in the budding yeast S. cerevisiae and identified CMR1 as a member in this network. Some 556 proteins were found binding to one or more histones, whereas only 25 proteins of these were found binding to the four core histones.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The 25 proteins include the four histones (H2A, H2B, H3 and H4), two units of the RPA complex (RFA2 and RFA3), two units of the Ku complex (YKU70 and YKU 80), many units of the RNA polymerase complex (RET1, RPO31, RPC17, RPC37, RPC40 and RPC82), many single-unit proteins (RIM1, YTA7, PSH1, CSE4, ABF2, CKA2, TIF3, DEM1, SUB2 and SMC3) and the previously uncharacterized protein YDL156W/CMR1. Then, associations with the CMR1 protein were investigated, and it was found that many proteins showed stable association with YDL156W, including the six proteins RIM1, RFA2, RFA3, YTA7, YKU70 and YKU80 which are within the 25 proteins found binding to all of the four core histones [12]. …”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation